DETERMINATION OF PARKING FACILITIES, PARKING RATES PARKING FACILITIES AND PARKING SUPERVISION TOWARDS SERVICE QUALITY THROUGH PARKING SERVICE USER SATISFACTION - Yoana Badra; Chablullah Wibisono; Mohamad Gita Indrawan (International Journal of Economic, Business, Accounting, Agriculture Management and Sharia Administration (IJEBAS), 2024)
Agency are performance indicators of the State Civil Apparatus of the Transportation Agency in providing services to the community by managing parking. The increasing number of residents and vehicles is a challenge for the Transportation Agency to improve performance through services to achieve satisfaction for parking service users. Data collection using questionnaires and distributed to 100 respondents. Statistical data analysis using SEM-PLS (Structural Equation Modeling Partial Least Square) and using path analysis to test the relationship pattern that reveals the influence of variables on other variables, both direct and indirect. The results of the study indicate that Parking Facilities directly determine positive and significant effects on service quality with P-Values ​​of 0.003 <0.05. Parking Rates directly determine negative and significant effects on service quality with P-Values ​​of 0.005 <0.05. Parking supervision determines positive and significant effects on service quality with P-Values ​​of 0.001 <0.05. Parking service user satisfaction directly has a positive and significant effect on service quality with P-values ​​of 0.008 <0.05. Parking facilities directly determine negatively and insignificantly on parking service user satisfaction with P-values ​​of 0.572 > 0.05. Parking rates directly determine positively and significantly on service quality with P-values ​​of 0.003 <0.05. Parking supervision directly has a positive and significant effect on service quality with P-values ​​of 0.001 <0.05. Parking service user satisfaction mediates the determination of parking facilities on service quality with a p-value of 0.620 > 0.05. Parking service user satisfaction mediates the determination of parking rates on service quality with a p-value of 0.073 > 0.05. User satisfaction of parking services mediates the influence of parking supervision on service quality with a p-value of 0.018 < 0.05.